Analisis Penerapan PSAK 105 Perhitungan Bagi Hasil Mudharobah Pada Bank BJB Syariah KCP Lippo Cikarang - Abdul Rojak; Dudang Gojali (Jurnal Bisnis Inovatif dan Digital, 2025)
This study aims to analyze the implementation of PSAK 105 related to the calculation of mudharabah profit sharing at Bank BJB Syariah KCP Lippo Cikarang. The research method used is qualitative with a descriptive approach, where data is collected through interviews, observations, and documentation. The analysis is carried out by comparing the practice of calculating mudharabah profit sharing at the bank with the provisions stipulated in PSAK 105, which includes aspects of recognition, measurement, presentation, and disclosure of mudharabah transactions. The results of the study indicate that in general Bank BJB Syariah KCP Lippo Cikarang has implemented the principles of PSAK 105 in calculating mudharabah profit sharing, but there are still several obstacles such as employee understanding of sharia accounting standards, optimization of information technology systems, and internal socialization regarding standard updates. These findings emphasize the importance of improving human resource competency and strengthening the supervision system so that the implementation of PSAK 105 can run optimally and support transparency and accountability of sharia bank financial reports.